The Logical Integrity of Thinking - Černienė, Bronislava (Problemos, 1975)
The author’s point of view is that the production of elementary tools testifies to the development of logical thinking. Attempts to find some intermediate forms of thinking between the perceptual image and logical thinking are considered groundless.